2020
DOI: 10.1002/mp.14422
|View full text |Cite
|
Sign up to set email alerts
|

Complete abdomen and pelvis segmentation using U‐net variant architecture

Abstract: Purpose Organ segmentation of computed tomography (CT) imaging is essential for radiotherapy treatment planning. Treatment planning requires segmentation not only of the affected tissue, but nearby healthy organs‐at‐risk, which is laborious and time‐consuming. We present a fully automated segmentation method based on the three‐dimensional (3D) U‐Net convolutional neural network (CNN) capable of whole abdomen and pelvis segmentation into 33 unique organ and tissue structures, including tissues that may be overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Alirr (2020) [ 24 ] segmented the liver based on a machine learning algorithm and found that the Dice of the segmented CT image was 0.726. Weston et al (2020) [ 25 ] established a liver segmentation method based on the CNN algorithm, and the results showed that the Dice value of this method for segmenting liver CT images was 0.79. Chen et al (2021) [ 26 ] optimized the model based on the FCN algorithm and applied it to liver segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Alirr (2020) [ 24 ] segmented the liver based on a machine learning algorithm and found that the Dice of the segmented CT image was 0.726. Weston et al (2020) [ 25 ] established a liver segmentation method based on the CNN algorithm, and the results showed that the Dice value of this method for segmenting liver CT images was 0.79. Chen et al (2021) [ 26 ] optimized the model based on the FCN algorithm and applied it to liver segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The neural network structure was developed based on the attention U-Net with a point rend module. The U-Net convolutional neural network can automatically segment CT images and has achieved high accuracy in recognizing abdominal organs and tissues ( 16 ). The point rend module was used to provide point-based predictions to further enhance segmentation performance ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…A few models have targeted a multi-slice approach, and BodySegAI demonstrates similar or higher Dice scores than these. 13,18,22,25,39…”
Section: Multi-slice Modellingmentioning
confidence: 99%